2015
DOI: 10.1155/2015/185821
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Potential of Crude Extract of Curvularia lunata, an Endophytic Fungi Isolated from Cymbopogon caesius

Abstract: Cymbopogon caesius grass is an aromatic tall grass species which grows in waste field and along the edges of crop fields in Karnataka. From this grass fungal endophytes were isolated on PDA medium and identified as Curvularia lunata. The fungus was cultured on Potato Dextrose broth for production of fungal metabolites. Ethyl acetate extract of the C. lunata was obtained by liquid-liquid partition of broth of endophyte and evaporation. Dried crude extract was tested for antimicrobial activity by agar well diffu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…indicating their importance as talented and major sources of bioactive molecules [9, 44]. However, the fungal metabolites have increased the interest in biomolecules activity studies [10].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…indicating their importance as talented and major sources of bioactive molecules [9, 44]. However, the fungal metabolites have increased the interest in biomolecules activity studies [10].…”
Section: Resultsmentioning
confidence: 99%
“…Endophytic fungi Curvularia sp. including Curvularia trifolii [9] and Curvularia lunata [10] provide a broad variety of bioactive secondary metabolites including polyketides and steroids. The genus Curvularia includs more than 40 species of saprophytes, endophytes and pathogens [11].…”
Section: Introductionmentioning
confidence: 99%
“…The pure culture of X. adscendens was inoculated in 1000ml Erlenmeyer flask containing 500ml of Potato dextrose broth on a rotary shaker for 15-22 days at 25° by fermentation method (Fig. 3.C) The culture filtrate was filtered and extracted with the same volume of Ethyl acetate twice and the extract was rotary evaporator dried for further analysis (Avinash et al, 2015). The ethyl acetate crude extract was analysed by HR-LCMS.…”
Section: Secondary Metabolite Extractionmentioning
confidence: 99%
“…crude extracts have promising antibacterial activities. The extract of C. lunata showed antibacterial activities against S. aureus and S. typhi [17], and the ethyl acetate crude extract of C. tuberculata has shown antibacterial activities against S. aureus, E. coli and P. aeruginosa [39]. Moderate activities of extract of Curvularia B34 against Bacillus subtilis, Listeria monocytogenes and Salmonella bacteria have been observed [37].…”
Section: Antibacterial Activity Of Crude Extractmentioning
confidence: 99%
“…Many species are known to be plant pathogens [16]. Some researchers have demonstrated that crude extracts of some Curvularia species have interesting properties including antimicrobial, antioxidant, phytotoxicity and leishmanicidal activities [12,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%